Starch hybrid nanocrystal modified EC / PEG-based multifunctional nanocomposite material and application thereof
By introducing starch hybrid nanocrystals into EC/PEG composites, the interface compatibility and functionality are improved, and the problems of insufficient performance and functions of EC/PEG composites are solved, and the high performance and wide application of multifunctional nanocomposites are achieved.
Patent Information
- Application Number
- CN202411956718.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-03-28
AI Technical Summary
The existing EC/PEG composite materials have poor performance in mechanical properties, water vapor barrier, oxygen barrier, ultraviolet protection, etc., and lack antioxidant activity, antibacterial, pH response discoloration, ammonia-sensitive discoloration, etc., which limits its application in smart food packaging and other fields.
Starch hybrid nanocrystals are used as functional fillers for EC/PEG blends, and EC/PEG-based multifunctional nanocomposites are developed by improving interfacial compatibility, enhancing mechanical properties and functionality.
It significantly improves the mechanical strength, toughness, water vapor barrier, oxygen barrier, ultraviolet protection and other properties of EC/PEG composite film materials, and gives them antioxidant activity, antibacterial, pH response discoloration, ammonia-sensitive discoloration and other functions, enhancing its application value in smart food packaging, antibacterial materials and other fields.
Smart Images

Figure CN119708651A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer nanocomposite materials, and specifically relates to EC / PEG-based multifunctional nanocomposite materials modified by starch hybrid nanocrystals and applications thereof. Background Art
[0002] In recent years, with the development of social economy and the improvement of people's consumption level, the consumption of food packaging materials has increased day by day, and smart food packaging materials have received more and more attention in the food industry. Ethylcellulose (EC) is a non-ionic cellulose ether generated by the reaction of cellulose with ethyl chloride after alkalization. The hydroxyl groups on the cellulose main chain are partially replaced by ethyl groups. It has excellent properties such as good solvent resistance, biodegradability, biocompatibility and film-forming properties. It is usually used as a fresh-keeping film in the field of food packaging. However, the strong interaction between EC molecules makes the EC film have poor ductility. Polyethylene glycol (PEG) is a hydrophilic polymer formed by the polymerization of ethylene oxide units. It has good dispersibility, film-forming properties, ductility, biocompatibility, transparency and other properties. It has a wide range of applications in the fields of pharmaceuticals, food packaging, medicine, etc. Blending polyethylene glycol (PEG) with ethyl cellulose (EC) can combine the advantages of both, so that it is expected to obtain EC / PEG-based composite materials with relatively excellent performance. However, due to certain differences in structure between PEG and EC, their compatibility is limited, resulting in poor mechanical properties, water vapor barrier, oxygen barrier, ultraviolet protection and other properties of EC / PEG composite film materials, and also lacking antioxidant activity, antibacterial, pH responsive color change, ammonia sensitive color change and other functions, which affects the practical application of EC / PEG composite materials in the fields of smart food packaging materials. Therefore, based on the deficiencies in the above-mentioned properties and functions of EC / PEG composite materials, the present invention creates a new type of starch hybrid nanocrystal, which is used as a functional filler of EC / PEG blends to improve the interfacial compatibility, mechanical properties, water vapor barrier, oxygen barrier, ultraviolet protection, antioxidant activity, antibacterial, pH responsive color change, ammonia sensitive color change and other properties of EC / PEG composite film materials, and develops a new type of EC / PEG-based multifunctional nanocomposite material, broadening its application in the fields of smart food packaging, antibacterial materials, antioxidant materials, pH responsive materials, ammonia detection, ultraviolet protection, environmental monitoring and safety. Summary of the invention
[0003] The purpose of the present invention is to provide a starch hybrid nanocrystal modified EC / PEG-based multifunctional nanocomposite material and a preparation method thereof in view of the deficiencies of the prior art. The EC / PEG-based multifunctional composite film material has excellent mechanical strength, toughness, water vapor barrier, oxygen barrier, ultraviolet protection, antioxidant activity, antibacterial, pH-responsive color change, ammonia-sensitive color change, and biodegradability. It can sense and share the pH value change of food during the spoilage process and has certain biological activity. Therefore, it is expected to effectively extend the shelf life of food while also providing real-time intelligent indication of the freshness of food. The preparation process of the multifunctional nanocomposite material is simple and environmentally friendly, low in cost, and suitable for mass production.
[0004] The technical solution of the present invention:
[0005] The invention provides a starch hybrid nanocrystal-modified EC / PEG-based multifunctional nanocomposite material, which is characterized in that it consists of the following components in parts by weight: 135 parts of ethyl cellulose, 15 parts of polyethylene glycol, 3 parts of L-ascorbic acid, and 1.5-6 parts of starch hybrid nanocrystals.
[0006] The preparation method of the starch hybrid nanocrystal comprises the following steps:
[0007] (1) Weigh 150 parts of potato starch and dissolve it in 5000 parts of deionized water. Stir it at room temperature for 30 min to make it dispersed evenly to obtain a uniform potato starch solution. Then stir it at 90°C and 1500 rpm for 1 h until the starch is completely gelatinized and set aside.
[0008] (2) adding 5000 parts of ethanol to the starch solution gelatinized in step (1), continuing to stir at 90°C and 1500 rpm for 90 min, then stopping heating, and cooling the potato starch dispersion to room temperature at 1500 rpm for later use;
[0009] (3) adding 5000 parts of ethanol to the potato starch dispersion obtained in step (2), and continuing stirring at room temperature and 1500 rpm for 70 minutes to obtain a milky white potato starch nanocrystal dispersion, and then centrifuging, washing with ethanol, and freeze-vacuum drying in sequence to obtain potato starch nanocrystals for later use;
[0010] (4) dispersing 10 parts of potato starch nanocrystals in 4000 parts of ethanol, stirring at room temperature to obtain a uniform potato starch nanocrystal dispersion for later use;
[0011] (5) Weigh 30.44 parts of DL-mandelic acid and dissolve it in 3500 parts of ethanol to obtain a uniform DL-mandelic acid solution for later use;
[0012] (6) adding the DL-mandelic acid solution obtained in step (5) to the potato starch nanocrystal dispersion obtained in step (4), stirring at room temperature for 1 hour to obtain a uniform blended solution for later use;
[0013] (7) Weigh 27.80 parts of ferrous sulfate heptahydrate and dissolve it in 500 parts of deionized water to obtain a uniform ferrous sulfate solution for later use;
[0014] (8) The ferrous sulfate solution obtained in step (7) is added to the mixed solution obtained in step (6), and the mixture is stirred at room temperature for 30 minutes, and then centrifuged, washed with ethanol, and vacuum dried to obtain starch hybrid nanocrystals.
[0015] The preparation method of the starch hybrid nanocrystal-modified EC / PEG-based multifunctional nanocomposite material comprises the following steps:
[0016] (1) Add 135 parts of ethyl cellulose and 15 parts of polyethylene glycol to 3000 parts of ethanol, stir at room temperature for 10 minutes, and then stir in a water bath at 55°C for 30 minutes to completely dissolve them to obtain a uniform blend solution, cool to room temperature, and set aside;
[0017] (2) Weigh 3 parts of L-ascorbic acid and dissolve it in 500 parts of ethanol at room temperature to obtain a uniform L-ascorbic acid solution for later use;
[0018] (3) adding 1.5 to 6 parts of starch hybrid nanocrystals to the L-ascorbic acid solution obtained in step (2), and stirring at room temperature for 20 min to obtain a uniform starch hybrid nanocrystal dispersion for later use;
[0019] (4) adding the starch hybrid nanocrystal dispersion obtained in step (3) to the blended solution obtained in step (1), and stirring at room temperature for 30 min to obtain a uniform film-forming solution for later use;
[0020] (5) The film-forming solution obtained in step (4) was poured into a flat-bottomed glass dish and dried in a vacuum oven at 55° C. for 48 h to obtain a starch hybrid nanocrystal-modified EC / PEG-based multifunctional nanocomposite material.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The EC / PEG-based multifunctional nanocomposite material prepared by the present invention has excellent mechanical strength, toughness, water vapor barrier, oxygen barrier, ultraviolet protection and other properties, and also has antioxidant activity, antibacterial, pH-responsive color change, ammonia-sensitive color change and other functions. It can sense and share the pH value changes of food during the spoilage process, and can provide real-time intelligent indication of the freshness of meat foods such as shrimps. The preparation process of the multifunctional nanocomposite material is simple and environmentally friendly, with low cost, and is suitable for large-scale production. It has wide application value in the fields of intelligent food packaging, antibacterial materials, antioxidant materials, pH-responsive materials, ammonia detection, ultraviolet protection, environmental monitoring and safety, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the potato starch nanocrystal involved in the present invention;
[0024] Figure 2 This is a scanning electron microscope image of the starch hybrid nanocrystal involved in the present invention;
[0025] Figure 3 This is a physical photo of the EC / PEG-based multifunctional nanocomposite material sample prepared in Example 3 of the present invention; DETAILED DESCRIPTION
[0026] The present invention is described in detail below through examples. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the contents of the present invention. The parts of the raw materials are all parts by weight unless otherwise specified.
[0027] In the specific embodiments and comparative example formulas, DL-mandelic acid is an analytically pure reagent provided by Shanghai Yuanye Biotechnology Co., Ltd., ferrous sulfate heptahydrate is an analytically pure reagent provided by Xilong Science Co., Ltd., ethanol is an analytically pure reagent provided by Tianjin Fuyu Fine Chemical Co., Ltd., ethyl cellulose is a product provided by Shanghai Yuanye Biotechnology Co., Ltd. (item number: S14026-500g), polyethylene glycol is a product provided by Ron Reagent Co., Ltd. (item number: R010816-500g), potato starch is a product provided by Ron Reagent Co., Ltd. (item number: R015072-500g), and L-ascorbic acid is an analytically pure reagent provided by Shandong Keyuan Biochemical Co., Ltd.
[0028] In the following specific embodiments and comparative example formulations and preparation methods, the preparation method of the starch hybrid nanocrystals comprises the following steps:
[0029] (1) Weigh 150 parts of potato starch and dissolve it in 5000 parts of deionized water. Stir it at room temperature for 30 min to make it dispersed evenly to obtain a uniform potato starch solution. Then stir it at 90°C and 1500 rpm for 1 h until the starch is completely gelatinized and set aside.
[0030] (2) adding 5000 parts of ethanol to the starch solution gelatinized in step (1), continuing to stir at 90°C and 1500 rpm for 90 min, then stopping heating, and cooling the potato starch dispersion to room temperature at 1500 rpm for later use;
[0031] (3) Add 5000 parts of ethanol to the potato starch dispersion obtained in step (2), and continue stirring at room temperature and 1500 rpm for 70 minutes to obtain a milky white potato starch nanocrystal dispersion, which is then centrifuged, washed with ethanol, and freeze-dried in a vacuum to obtain potato starch nanocrystals (the scanning electron microscope image of which is shown in FIG. Figure 1 ),spare;
[0032] (4) dispersing 10 parts of potato starch nanocrystals in 4000 parts of ethanol, stirring at room temperature to obtain a uniform potato starch nanocrystal dispersion for later use;
[0033] (5) Weigh 30.44 parts of DL-mandelic acid and dissolve it in 3500 parts of ethanol to obtain a uniform DL-mandelic acid solution for later use;
[0034] (6) adding the DL-mandelic acid solution obtained in step (5) to the potato starch nanocrystal dispersion obtained in step (4), stirring at room temperature for 1 hour to obtain a uniform blended solution for later use;
[0035] (7) Weigh 27.80 parts of ferrous sulfate heptahydrate and dissolve it in 500 parts of deionized water to obtain a uniform ferrous sulfate solution for later use;
[0036] (8) The ferrous sulfate solution obtained in step (7) was added to the mixed solution obtained in step (6), and the mixture was stirred at room temperature for 30 minutes, and then centrifuged, washed with ethanol, and vacuum dried to obtain starch hybrid nanocrystals (the scanning electron microscope image of which is shown in FIG. Figure 2 ).
[0037] Example 1
[0038] The EC / PEG-based multifunctional nanocomposite material modified by starch hybrid nanocrystals is characterized in that it is composed of the following components in parts by weight: 135 parts of ethyl cellulose, 15 parts of polyethylene glycol, 3 parts of L-ascorbic acid, and 1.5 parts of starch hybrid nanocrystals.
[0039] The preparation method comprises the following steps:
[0040] (1) Add 135 parts of ethyl cellulose and 15 parts of polyethylene glycol to 3000 parts of ethanol, stir at room temperature for 10 minutes, and then stir in a water bath at 55°C for 30 minutes to completely dissolve them to obtain a uniform blend solution, cool to room temperature, and set aside;
[0041] (2) Weigh 3 parts of L-ascorbic acid and dissolve it in 500 parts of ethanol at room temperature to obtain a uniform L-ascorbic acid solution for later use;
[0042] (3) adding 1.5 parts of starch hybrid nanocrystals to the L-ascorbic acid solution obtained in step (2), and stirring at room temperature for 20 min to obtain a uniform starch hybrid nanocrystal dispersion for later use;
[0043] (4) adding the starch hybrid nanocrystal dispersion obtained in step (3) to the blended solution obtained in step (1), and stirring at room temperature for 30 min to obtain a uniform film-forming solution for later use;
[0044] (5) The film-forming solution obtained in step (4) was poured into a flat-bottomed glass dish and dried in a vacuum oven at 55° C. for 48 h to obtain a starch hybrid nanocrystal-modified EC / PEG-based multifunctional nanocomposite material.
[0045] Example 2
[0046] The EC / PEG-based multifunctional nanocomposite material modified by starch hybrid nanocrystals is characterized in that it is composed of the following components in parts by weight: 135 parts of ethyl cellulose, 15 parts of polyethylene glycol, 3 parts of L-ascorbic acid, and 3 parts of starch hybrid nanocrystals.
[0047] The preparation method comprises the following steps:
[0048] (1) Add 135 parts of ethyl cellulose and 15 parts of polyethylene glycol to 3000 parts of ethanol, stir at room temperature for 10 minutes, and then stir in a water bath at 55°C for 30 minutes to completely dissolve them to obtain a uniform blend solution, cool to room temperature, and set aside;
[0049] (2) Weigh 3 parts of L-ascorbic acid and dissolve it in 500 parts of ethanol at room temperature to obtain a uniform L-ascorbic acid solution for later use;
[0050] (3) adding 3 parts of starch hybrid nanocrystals to the L-ascorbic acid solution obtained in step (2), and stirring at room temperature for 20 min to obtain a uniform starch hybrid nanocrystal dispersion for later use;
[0051] (4) adding the starch hybrid nanocrystal dispersion obtained in step (3) to the blended solution obtained in step (1), and stirring at room temperature for 30 min to obtain a uniform film-forming solution for later use;
[0052] (5) The film-forming solution obtained in step (4) was poured into a flat-bottomed glass dish and dried in a vacuum oven at 55° C. for 48 h to obtain a starch hybrid nanocrystal-modified EC / PEG-based multifunctional nanocomposite material.
[0053] Example 3
[0054] The EC / PEG-based multifunctional nanocomposite material modified by starch hybrid nanocrystals is characterized in that it is composed of the following components in parts by weight: 135 parts of ethyl cellulose, 15 parts of polyethylene glycol, 3 parts of L-ascorbic acid, and 6 parts of starch hybrid nanocrystals.
[0055] The preparation method comprises the following steps:
[0056] (1) Add 135 parts of ethyl cellulose and 15 parts of polyethylene glycol to 3000 parts of ethanol, stir at room temperature for 10 minutes, and then stir in a water bath at 55°C for 30 minutes to completely dissolve them to obtain a uniform blend solution, cool to room temperature, and set aside;
[0057] (2) Weigh 3 parts of L-ascorbic acid and dissolve it in 500 parts of ethanol at room temperature to obtain a uniform L-ascorbic acid solution for later use;
[0058] (3) adding 6 parts of starch hybrid nanocrystals to the L-ascorbic acid solution obtained in step (2), and stirring at room temperature for 20 min to obtain a uniform starch hybrid nanocrystal dispersion for later use;
[0059] (4) adding the starch hybrid nanocrystal dispersion obtained in step (3) to the blended solution obtained in step (1), and stirring at room temperature for 30 min to obtain a uniform film-forming solution for later use;
[0060] (5) The film-forming solution obtained in step (4) was poured into a flat-bottomed glass dish and dried in a vacuum oven at 55° C. for 48 h to obtain a starch hybrid nanocrystal-modified EC / PEG-based multifunctional nanocomposite material.
[0061] Comparative Example 1
[0062] As a comparison standard of the above embodiments, the present invention provides an EC / PEG composite material prepared without starch hybrid nanocrystals and L-ascorbic acid, comprising the following steps:
[0063] (1) Add 135 parts of ethyl cellulose and 15 parts of polyethylene glycol to 3000 parts of ethanol, stir at room temperature for 10 min, then stir in a water bath at 55 °C for 30 min to completely dissolve them to obtain a uniform blend solution, cool to room temperature, and set aside;
[0064] (2) Add 500 parts of ethanol to the blended solution obtained in step (1), and stir at room temperature for 30 minutes to obtain a uniform film-forming solution for later use;
[0065] (3) The film-forming solution obtained in step (2) was poured into a flat-bottomed glass dish and dried in a vacuum oven at 55° C. for 48 h to obtain an EC / PEG composite material.
[0066] Comparative Example 2
[0067] As a comparison standard for each of the above embodiments, the present invention provides an EC / PEG / L-ascorbic acid composite material prepared without starch hybrid nanocrystals, comprising the following steps:
[0068] (1) Add 135 parts of ethyl cellulose and 15 parts of polyethylene glycol to 3000 parts of ethanol, stir at room temperature for 10 min, then stir in a water bath at 55 °C for 30 min to completely dissolve them to obtain a uniform blend solution, cool to room temperature, and set aside;
[0069] (2) Weigh 3 parts of L-ascorbic acid and dissolve it in 500 parts of ethanol at room temperature to obtain a uniform L-ascorbic acid solution for later use;
[0070] (3) adding the L-ascorbic acid solution obtained in step (2) to the mixed solution obtained in step (1), and stirring at room temperature for 30 min to obtain a uniform film-forming solution for standby use;
[0071] (4) The film-forming solution obtained in step (3) was poured into a flat-bottomed glass dish and dried in a vacuum oven at 55° C. for 48 h to obtain an EC / PEG / L-ascorbic acid composite material.
[0072] Structure and performance test:
[0073] The EC / PEG-based composite material prepared in the comparative example and the EC / PEG-based multifunctional nanocomposite material prepared in the example were subjected to performance tests, wherein the tensile properties were tested by an electronic tensile testing machine, the UV-visible properties were tested by an UV spectrophotometer, and the average transmittance of ultraviolet rays (UVA, UVB and UVC) was calculated with reference to GB / T 18830-2009, the water vapor transmittance was tested according to ASTM E 96, the oxygen transmittance was tested according to GB / T 10004-2008, and the antibacterial activity was tested according to QBT 2591-2003.
[0074] The ammonia response test method is as follows: a small disc of composite material sample with a diameter of 1.2 cm is exposed to an ammonia environment for 30 seconds, the color change of the composite material is observed, and the color difference value ∆E of the composite material is measured with the help of a colorimeter (NR200) (Note: ∆E >3 indicates an obvious color change visible to the human eye).
[0075] The DPPH free radical scavenging rate test method is as follows: for the experimental group, 0.2 g of the membrane sample was cut into pieces and soaked in 5 mL of ethanol. After soaking for 24 h, 2 mL of the supernatant of the soaking solution was extracted and set aside; then, 1 ml of 50 mg / L DPPH solution was added to the 2 mL of the supernatant, and the mixture was shaken and placed in the dark at room temperature for 1 h; then, the absorbance of the mixture at 517 nm (denoted as A) was measured using an ultraviolet spectrophotometer. sample ); for the control group, 1 mL of 50 mg / L DPPH solution was added to 2 mL of ethanol, and the mixture was shaken and placed in the dark at room temperature for 1 h; then, the absorbance of the mixture at 517 nm (denoted as A) was measured by a UV spectrophotometer. control );DPPH free radical scavenging rate (%)=100*(A control -A sample ) / A control .
[0076] Shrimp freshness monitoring experiment: Fresh shrimps were purchased from the market, and the shrimps (mass: 100 g) were placed in a glass culture dish and sealed with a culture dish cover. The EC / PEG-based composite materials prepared in Comparative Examples 1 and 2 and the composite film of the EC / PEG-based multifunctional nanocomposite material modified with starch hybrid nanocrystals prepared in Example 3 were pasted under the cover (pre-cut into sample materials with a diameter of 1.2 cm). The above shrimp samples were then stored in an oven at 25°C, and the changes in the freshness of the shrimps and the color changes of the composite film sample materials were observed and recorded.
[0077] Table 1 Performance test data
[0078]
[0079] Table 2 Experimental data of shrimp freshness monitoring (where t is the storage time of fresh shrimp)
[0080]
[0081] The results of the ammonia response test show that the composite material prepared in Comparative Example 1 is colorless and transparent. After being exposed to an ammonia environment for 30 seconds, its color does not change significantly, and it still presents colorless and transparent optical properties, and its ∆E value is 0.13 (that is, the color difference is negligible and cannot be distinguished by the human eye); the composite material prepared in Comparative Example 2 is colorless and transparent. After being exposed to an ammonia environment for 30 seconds, its color does not change significantly, and it still presents colorless and transparent optical properties, and its ∆E value is 2.28 (that is, the color difference is negligible and cannot be distinguished by the human eye); the EC / PEG-based multifunctional nanocomposite prepared in Example 1 is light yellow, and after being exposed to an ammonia environment for 30 seconds, its color changes to light green, and its ∆E value is 5.23 (Note: ∆E>3 indicates an obvious color change visible to the human eye); the EC / PEG-based multifunctional nanocomposite prepared in Example 2 is light yellow, and after being exposed to an ammonia environment for 30 seconds, its color changes to light green, and its ∆E value is 9.15 (Note: ∆E >3 indicates an obvious color change visible to the human eye); the EC / PEG-based multifunctional nanocomposite prepared in Example 3 is yellow. After being exposed to an ammonia environment for 30 seconds, its color changes to green, and its ∆E value is 11.72 (Note: ∆E >3 indicates an obvious color change visible to the human eye).
[0082] The shrimp experiment results (see Table 2) prove that the EC / PEG-based multifunctional nanocomposite prepared in the example can efficiently, real-time and intuitively monitor the freshness changes of shrimp and other meat products during storage through the color changes of the membrane.
[0083] pH response experiment: The composite materials prepared in the comparative example and the example were cut into sample materials with a diameter of 1.2 cm, and 5 drops of a buffer solution with a pH value of 10 were dripped on the surface of the sample materials to observe their color changes. The experimental results show that after the buffer solution with a pH value of 10 was dripped on the surface of the composite materials prepared in comparative examples 1 and 2, the color did not change significantly, and the optical properties remained colorless; after the buffer solution with a pH value of 10 was dripped on the surface of the composite material prepared in Example 1, its color changed significantly (from light yellow to light green); after the buffer solution with a pH value of 10 was dripped on the surface of the composite material prepared in Example 2, its color changed significantly (from light yellow to light green); after the buffer solution with a pH value of 10 was dripped on the surface of the composite material prepared in Example 3, its color changed significantly (from yellow to green). The above results show that the EC / PEG-based multifunctional nanocomposite prepared by the present invention has a pH-responsive color-changing function.
[0084] In summary, it can be seen from the sample performance test data (see Tables 1 and 2) that the EC / PEG-based multifunctional nanocomposite prepared by the present invention has excellent mechanical strength, tensile elongation at break (i.e., ductility), toughness, water vapor barrier, oxygen barrier, ultraviolet protection and other properties, and also has excellent DPPH free radical scavenging rate (i.e., antioxidant activity), antibacterial, pH-responsive color change, ammonia-sensitive color change and other functions, and can provide real-time intelligent indication of the freshness of meat foods such as shrimps. In addition, the preparation process of the multifunctional nanocomposite is simple and environmentally friendly, with low cost, and is suitable for mass production. It has wide application value in the fields of intelligent food packaging, antibacterial materials, antioxidant materials, pH-responsive materials, ammonia detection, ultraviolet protection, environmental monitoring and safety, etc.
[0085] The content of the present invention is not limited to the embodiments listed. A person skilled in the art can make any equivalent changes to the technical solution of the present invention by reading the specification of the present invention, which are all covered by the claims of the present invention.
Claims
1. EC / PEG-based multifunctional nanocomposite material modified by starch hybrid nanocrystals, characterized in that: The invention is composed of the following components in parts by weight: 135 parts of ethyl cellulose, 15 parts of polyethylene glycol, 3 parts of L-ascorbic acid, and 1.5-6 parts of starch hybrid nanocrystals; The preparation method of the starch hybrid nanocrystal comprises the following steps: (1) Weigh 150 parts of potato starch and dissolve it in 5000 parts of deionized water. Stir it at room temperature for 30 min to make it dispersed evenly to obtain a uniform potato starch solution. Then stir it at 90°C and 1500 rpm for 1 h until the starch is completely gelatinized and set aside. (2) adding 5000 parts of ethanol to the starch solution gelatinized in step (1), continuing to stir at 90°C and 1500 rpm for 90 min, then stopping heating, and cooling the potato starch dispersion to room temperature at 1500 rpm for later use; (3) adding 5000 parts of ethanol to the potato starch dispersion obtained in step (2), and continuing stirring at room temperature and 1500 rpm for 70 minutes to obtain a milky white potato starch nanocrystal dispersion, and then centrifuging, washing with ethanol, and freeze-vacuum drying in sequence to obtain potato starch nanocrystals for later use; (4) dispersing 10 parts of potato starch nanocrystals in 4000 parts of ethanol, stirring at room temperature to obtain a uniform potato starch nanocrystal dispersion for later use; (5) Weigh 30.44 parts of DL-mandelic acid and dissolve it in 3500 parts of ethanol to obtain a uniform DL-mandelic acid solution for later use; (6) adding the DL-mandelic acid solution obtained in step (5) to the potato starch nanocrystal dispersion obtained in step (4), stirring at room temperature for 1 hour to obtain a uniform blended solution for later use; (7) Weigh 27.80 parts of ferrous sulfate heptahydrate and dissolve it in 500 parts of deionized water to obtain a uniform ferrous sulfate solution for later use; (8) The ferrous sulfate solution obtained in step (7) is added to the mixed solution obtained in step (6), and the mixture is stirred at room temperature for 30 minutes, and then centrifuged, washed with ethanol, and vacuum dried to obtain starch hybrid nanocrystals.
2. The method for preparing the EC / PEG-based multifunctional nanocomposite material modified by starch hybrid nanocrystals according to claim 1, characterized in that The steps include: (1) Add 135 parts of ethyl cellulose and 15 parts of polyethylene glycol to 3000 parts of ethanol, stir at room temperature for 10 minutes, and then stir in a water bath at 55°C for 30 minutes to completely dissolve them to obtain a uniform blend solution, cool to room temperature, and set aside; (2) Weigh 3 parts of L-ascorbic acid and dissolve it in 500 parts of ethanol at room temperature to obtain a uniform L-ascorbic acid solution for later use; (3) adding 1.5 to 6 parts of starch hybrid nanocrystals to the L-ascorbic acid solution obtained in step (2), and stirring at room temperature for 20 min to obtain a uniform starch hybrid nanocrystal dispersion for later use; (4) adding the starch hybrid nanocrystal dispersion obtained in step (3) to the blended solution obtained in step (1), and stirring at room temperature for 30 min to obtain a uniform film-forming solution for later use; (5) The film-forming solution obtained in step (4) was poured into a flat-bottomed glass dish and dried in a vacuum oven at 55° C. for 48 h to obtain a starch hybrid nanocrystal-modified EC / PEG-based multifunctional nanocomposite material.
3. The use of the EC / PEG-based multifunctional nanocomposite material modified by starch hybrid nanocrystals according to claim 1, characterized in that: It can be applied to smart packaging materials, UV barrier materials, pH response materials, visual detection of ammonia, antibacterial materials, antioxidant materials, environmental monitoring and safety fields.